Design of Arrangement of Working Time to Increase Productivity of the Workers by Using Flat Iron at Garment “A” - I Made Anom Santiana; M. Yusuf (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The garments businesses in Bali grow quickly in line with the growth of tourism industry. These are proven by presence of many garment businesses in big scale investment with hundreds of workers or small -scale investments of home industries. However, the level of awareness and the failure of the business managers to seek for comfort, health, and safety for their workers remains very low. One of many problems that important in garment business for the workers in flat iron is musculoskeletal disorder. Generally, the working position is in the standing position for long time, and the hot temperature of environment resulted in the flat iron radiation. Workers that use flat iron work 9 hours per day including the lunch break and 7 day a weak, except for the big holidays or when there is less order. They start working at 08.00 a.m. until 17.00 p.m. with lunch break at 12.00 until 13.00 p.m. Arrangement for the working time and the break time, holiday, working shifts, are one of the many aspects in organization that needs to be paid attention because by arranging the working time, it may make them comfortable, safe, healthy, so it can increase the work productivity. Increasing the working time will cause the accumulating fatigues and in turn, it will decrease the productivity. Therefore, to solve that problems, this research has been done experimentally by arranging the working time, namely by providing 10 minute-breaks every two hours of working time while drinking tea. This research was conducted to 12 female workers who used flat iron in “A” garment, of Tabanan Regency, Bali, with treatment by subject design. The indicated workload was measured by heart rate with pulse meter. Musculoskeletal disorder was predicted by Nordic Body Map questionnaire. Data were analyzed by t test on 5% significant. The result of analysis showed that there was a decrease of workloads and the subjective disorders significantly before and after treatment as well as the increase of the working productivity significantly (p<0,05).